Search for heavy long-lived multi-charged particles in pp collisions at $\sqrt{s}=\;8$ TeV using the ATLAS detector - ATLAS collaboration (2825 authors) (2015)
A search for heavy long-lived multi-charged particles is performed using the ATLAS detector at the LHC. Data collected in 2012 at $\sqrt{s}=8$  TeV from pp collisions corresponding to an integrated luminosity of 20.3 fb$^{-1}$ are examined. Particles producing anomalously high ionisation, consistent with long-lived massive particles with electric charges from $|q|=2e$ to $|q|=6e$ are searched for. No signal candidate events are observed, and 95 % confidence level cross-section upper limits are interpreted as lower mass limits for a Drell–Yan production model. The mass limits range between 660 and 785 GeV.